Towards improved butanol production through targeted genetic modification of Clostridium pasteurianum - Schwarz, Katrin; Grosse-Honebrink, Alexander; Derecka, Kamila; Rotta, Carlo; Zhang, Ying; Minton, Nigel P. (Elsevier, 2017)
Declining fossil fuel reserves, coupled with environmental concerns over their continued extraction and exploitation have led to strenuous efforts to identify renewable routes to energy and fuels. One attractive option is to convert glycerol, a by-product of the biodiesel industry, into n-butanol, an industrially important chemical and potential liquid transportation fuel, using Clostridium pasteurianum. Under certain growth conditions this Clostridium species has been shown to predominantly produce n-butanol, together with ethanol and 1, 3-propanediol, when grown on glycerol. Further increases in the yields of n-butanol produced by C. pasteurianum could be accomplished through rational metabolic engineering of the strain. Accordingly, in the current report we have developed and exemplified a robust tool kit for the metabolic engineering of C. pasteurianum and used the system to make, for the first time, in-frame deletion mutants of pivotal genes involved in solvent production, namely hydA (hydrogenase), rex (Redox response regulator) and dhaBCE (glycerol dehydratase). We were, for the first time in C. pasteurianum, able to eliminate 1, 3-propanediol synthesis and demonstrate its production was essential for growth on glycerol as a carbon source. Inactivation of both rex and hydA resulted in increased n-butanol titres, representing the first steps towards improving the utilisation of C. pasteurianum as a chassis for the industrial production of this important chemical.